Study of the influence of muscle activation on a driver's lower extremity injury. Issue 3 (3rd May 2016) - Gao, Zhenhai; Li, Chuzhao; Hu, Hongyu; Zhao, Hui; Chen, Chaoyang; Yu, Huili
ABSTRACT: A driver's muscle activation of lower extremity at a collision moment ( A COL ) was precisely described and the influence on injury was investigated. A simulated collision scene was constructed and 10 young male volunteers were recruited for the field test. A COL of eight major lower extremity muscles were measured. The injury in this muscle activation state was analysed through a simulation and compared with those in minimum, median and maximum activation states. A COL at 4.1%–22.6% were significantly smaller than fully activated with 100%. Compared with the minimum state, the injury parameters in maximum muscle activation state increased for at least 45%. Muscles are not always in maximum or even median activation at a collision moment. With the increase of muscle activation, the injury will potentially increase and the peak moment of injury parameters will delay. Therefore, muscle activation should be considered in injury analysis and the passive vehicle safety system design.